Laboratory assessment of the therapeutic potential of new penicillins and other antibiotics - Sutherland, R. (The University of Edinburgh, 1979)
The introduction of a novel antibiotic or antibaoterial agent into clinical practice is the culmination of several years work by relatively large numbers of specialists in widely different fields of science. The details of the testing procedures employed in the selection of the compound of choice from a large number of candidates will vary, depending upon the nature of the substance being evaluated, but the general principles remain the same.

Thus, although the final proof of the value of an anti¬ baoterial agent is the olinical result obtained when the drug is used to treat infection it is clearly impracticable to evaluate new drugs by clinical trial alone. Consequently, the therapeutio potential of a novel antibiotic must be assessed by study of seleoted parameters in the laboratory. These include measurement of antibaoterial activity in vitro and in vivo, and studies of the absorption, distribution and metabolism of the drug in animals and healthy volunteers. The toxicology of the compound is also of great importance and is a factor which calls for the generation of vast amounts of data from animal studies.

In addition to the evaluation data generated during the selection or assessment procedures, other parameters are of importance. For instance, knowledge of the interaction of the test compound with other available drugs, of the mode of action, and of the rate of development of resistance, provides information to be considered in the assessment of activity. Moreover, the potential value of a compound whioh is in clinical use may be greatly affected by the emergence of resistant bacteria and understanding of this is important as part of ongoing evaluation.

The sections below illustrate the factors involved in the laboratory evaluation of new antibiotics and in the assessment of the therapeutic potential of these drugs, by reference to experi¬ mental data obtained in my laboratory in investigations with novel penicillins or other antibacterial substances.